2020
DOI: 10.1038/s41586-020-2199-7
|View full text |Cite
|
Sign up to set email alerts
|

The gut–brain axis mediates sugar preference

Abstract: Summary The taste of sugar is one of the most basic sensory percepts for humans and other animals. Remarkably, animals can develop a strong preference for sugar even if lacking sweet taste receptors, pointing to a mechanism independent of taste 1 – 3 . Here we examined the neural basis for sugar preference and demonstrate that a population of neurons in the vagal ganglia and brainstem are activated via the gut-brain axis to create preference for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
207
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(219 citation statements)
references
References 59 publications
11
207
1
Order By: Relevance
“…The presence of oral sweet taste receptors in the intestinal tract are known to enhance the intake and preference for sugar-rich foods and mediate GLP-1 release [ 57 ]. Our finding of increases in GLP-1 and PYY associated with RYGB support this mechanism and highlight the potential role of the gut-brain axis in mediating sugar preference recently described in rodents [ 58 ].…”
Section: Discussionsupporting
confidence: 86%
“…The presence of oral sweet taste receptors in the intestinal tract are known to enhance the intake and preference for sugar-rich foods and mediate GLP-1 release [ 57 ]. Our finding of increases in GLP-1 and PYY associated with RYGB support this mechanism and highlight the potential role of the gut-brain axis in mediating sugar preference recently described in rodents [ 58 ].…”
Section: Discussionsupporting
confidence: 86%
“…Clozapine was used to activate DREADDs ( Gomez et al, 2017 ; Tan et al, 2020 ). Although there are concerns ( Ilg et al, 2018 ) about potential off-target effects of this compound, Ilg et al (2018) found no evidence thatlow-dose clozapine affected working memory.…”
Section: Methodsmentioning
confidence: 99%
“…Opto-and chemogenetic experiments showed that nodose vagal sensory neurons are necessary for post-ingestive fat mediated reward (Han et al, 2018). A population of neurons in brainstem that receive sugar signals from the vagus were chemogenetically activated to create preferences to otherwise less-preferred sweet stimuli (Tan et al, 2020). Together, these pre-clinical findings reveal a gut-to-brain post-ingestive fat and sugar-sensing pathway critical for the development of food preference.…”
Section: Introductionmentioning
confidence: 99%